Misconception and scientific attitude of teacher towards elementary school geometry assessed from information technology transformation - Bistari, Bistari; Mumtazah, Nadia Wardah; Fitriawan, Dona; R, Zubaidah; Hamdani, Hamdani (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
There is a misconception about elementary school geometry material that makes the teacher's scientific attitude in implementing learning in the classroom still not optimal and causes the application of IT transformation to be uneven. This research aims to describe the misconceptions about geometry among elementary school teachers, the scientific attitudes of elementary school teachers in the process of learning geometry, and how elementary school teachers overcome misconceptions and optimize scientific attitudes learned from the role of IT. The subjects of this study were 171 teachers from 18 districts and cities. The research was conducted in a descriptive qualitative form by giving questionnaires about elementary school geometry concepts and teachers' scientific attitudes toward learning, analyzing answers according to criteria, and exploring the relationship between misconceptions and scientific attitudes learned from IT transformation. The results of this study indicate that conceptual errors were found in the research subjects, which included generalization and specialization misconceptions; the teacher's scientific attitude influences the misconceptions experienced; and the role of IT can help calculate and visualize abstract things in learning. The application of IT in the learning process shows good results for overcoming teachers' misconceptions and scientific attitudes, and of course, it can be an option for teachers to be able to apply it with various IT-based learning media that attract students' learning interests.